2021
DOI: 10.21512/ijobex.v2i2.7138
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Enablers, Barriers and Opportunities to Digital Supply Chain Management in Vietnamese Manufacturing Smes

Abstract: This paper examines the enablers, barriers and opportunities of digital supply chain management (DSCM) in manufacturing Small and Medium-sized Enterprises (SMEs) in Vietnam fromexpert’s perspective. The study is a foundational effort to contribute to the establishment of new digital management era in many emerging economies. Applying a systematic literature review (SLR) of relevant studies and a qualitative data methodology this research also aims to explore the factors affecting technology adoption in supplyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This study found out that SMEs would need broader networks and support to adopt the new technologies as digitalisation of industries is being carried out differently in distinct nations and they cannot develop the value chain in isolation (Phuc, Kumar & Ruan, 2019). This creates opportunities for SMEs to gain access to existing knowledge and create a resilient system and processes in the future (Radanliev, Roure, Nurse, Montalvo & Burnap, 2019).…”
Section: Important Key Factors Of 4ir Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found out that SMEs would need broader networks and support to adopt the new technologies as digitalisation of industries is being carried out differently in distinct nations and they cannot develop the value chain in isolation (Phuc, Kumar & Ruan, 2019). This creates opportunities for SMEs to gain access to existing knowledge and create a resilient system and processes in the future (Radanliev, Roure, Nurse, Montalvo & Burnap, 2019).…”
Section: Important Key Factors Of 4ir Adoptionmentioning
confidence: 99%
“…The study also is of beneficial from an academic as well as a managerial point of view. Leaders and management can be able to identify the skill gaps within their organisation which may require rearrangement of staffs who mismatched positions or cannot be reskilled or upskilled to work with the new technologies' application (Phuc Khanh Linh et al, 2019) which are brought by digital era to transform businesses, quickly seize opportunities, and mitigate risks from digital transformation.…”
Section: Introductionmentioning
confidence: 99%